MERDEKA DARI IMPRIALISME-KOLONIALISME MENUJU IDENTITAS NASIONAL SERTA MENEGAKKAN KONSTITUSI UNTUK NKRI DAN UPETI DARI RAKYAT UNTUK BIROKRAT - Walikrom, Achmad Anton Rizqika (Academy of Education Journal, 2023)
Indonesian independence was achieved with a sense of nationalism and patriotism as well as the struggle of the Indonesian people both in the "Government, Traders, Aristocrat, Clerics and Marginal Communities" to fight "Colonialism and Imprialism" because they saw Indonesian in the face of the Dutch in a long gap of three and a half times century if calculated 350 years. National identity is known from the aspirations of young people, those who are educated who want to have ambition to be independent with the struggle and fate of suffering the same since the invaders like the State that first entered in Indonesian "Portuguese, Spanish, English, Dutch and Japanese" but a country with the nickname three "G" namely (Gold, Glory and Gospel) such as looking for "Glory, Looking for logistics or spices, Spreading the holy mission of Christianity and Catholicism" with the dominance of this young people want a revolution like countries that want independence. National identity can not be separated from regulations or constitutions that imitate developed countries from kingdoms or monarchies to a republic with democracy in each government Different axis there is a axis "Communist and there is a Liberalist axis" and this has become a culture of Indonesian government since the Order long time, new order until the Reformation Era. Taxes or tribute are collected from employees and employees or laborers, BUMS (private-owned business entities), BUMN (private mili-business entities) to be transferred to the government as procurement of "Infrastructure, Logistics, Pharmacy, Social, Education, Culture, Religion" in essence State cooking is spent in each region for the needs of the respective regional autonomy.